2019
DOI: 10.1016/j.tim.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Can Ebola Virus Vaccines Have Universal Immune Correlates of protection?

Abstract: Testing vaccine efficacy against the highly lethal Ebola virus (EBOV) in humans is almost impossible due to obvious ethical reasons and the sporadic nature of outbreaks. For such situations, the 'animal rule' was established, requiring the product be tested in animal models, expected to predict the response observed in humans. For vaccines, this testing aims to identify immune correlates of protection, such as antibody or cell-mediated responses. In the wake of the 2013-2016 EBOV epidemic, and despite advancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 68 publications
1
24
0
Order By: Relevance
“…Recently, some authors have suggested that different CoP might have to be utilized for different EBOV vaccines [36] depending, among other parameters, on the antigen used and the route of vaccination. Thus, we need to apply caution when using solely antibody titration to assess the effectiveness of putative vaccines, as this alone may not reflect immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some authors have suggested that different CoP might have to be utilized for different EBOV vaccines [36] depending, among other parameters, on the antigen used and the route of vaccination. Thus, we need to apply caution when using solely antibody titration to assess the effectiveness of putative vaccines, as this alone may not reflect immunity.…”
Section: Discussionmentioning
confidence: 99%
“…The Ebola crisis calls for a sense of urgency towards the TB epidemic, and for a narrowed focus. For example, the lack of knowledge of correlates of protection has not prevented the advancement of a new malaria, polio [46], or Ebola vaccine [47,48], neither the eradication of small pox [49]. Funds can be prioritized for pre-clinical development and field testing of candidates in order to stop the scourge, else the goal of TB elimination will remain elusive [1].…”
Section: Discussionmentioning
confidence: 99%
“…The Ebola crisis calls for a sense of urgency towards the TB epidemic, and for a narrowed focus. For example, the lack of knowledge of correlates of protection has not prevented the advancement of a new malaria, polio (46), or Ebola vaccine (47,48), neither the eradication of small pox (49). Funds can be prioritized for pre-clinical development and eld testing of candidates in order to stop the scourge, else the goal of TB elimination will remain elusive (1).…”
Section: Discussionmentioning
confidence: 99%